HISTORY OF FORMATION PALAEO-DELTAS OF LOWER VOLGA DELTAS - Georgy Rychagov; Vladislav Korotaev; Aleksey Chernov (Geography, Environment, Sustainability)
The palaeo-Volga River valley existed within the present-day Lower Volga region during the last 600–700 ka. Its lower parts periodically transformed into a long and deep ingressional estuary with the apex location controlled by the amplitude of the Caspian Sea level rise. Between the Early Khvalinian highstand of +50 m and the Early Holocene Mangyshlak lowstand at -100 m, the apex of the Volga Delta has wandered 700 km alongstream. The estuarine-marine and alluvial environments in the ingressional estuary in the area between the present-day cities of Volgograd and Astrakhan, were changing throughout the entire Late Pleistocene and Holocene. The associated succession reflects a complex history of the Caspian Sea level oscillations. Only over the last 16 ka, there have been six marine (estuarine) phases within the Volga-Akhtuba valley correspondent to the Late Khvalinian and Novocaspian transgressions. The transgressions alternated with regressive phases associated with the dominance of alluvial environments in the Lower Volga valley. There are pronounced traces of three transgressive-regressive phase alternations of the Late Khvalinian and Novocaspian ages in the modern Volga-Akhtuba floodplain topography, that correlate with four generations of ancient floodplain and delta surfaces distinguished in this study. Surfaces of different age generations differ in absolute and relative heights, morphological types of floodplain topography, and present-day vegetation.